The psychological characteristics of the college environment and their implications for Foundation College - Sinco, Edelmira D. ([Quezon City s.n.], 1964)
This study presents the use of needpress instruments-- the College Characteristics Index and the Activities Index-- to determine the need and press factor agreements at the Foundation College.
Thesis (M.Ed.)--University of the Philippines
Keywords: Foundation College, Dumaguete City; Universities and colleges